Validity and Reliability of the Kannada Version of the Parenting Styles and Dimensions Questionnaire-Short Form - B. Sapna; D. S. Gazala Sulthana (Journal of Indian Association of Public Health Dentistry)
Background: Parenting style is an important determinant in the field of dentistry to understand children’s oral health outcomes. Objective: The aim of this study was to translate the Parenting Styles and Dimensions Questionnaire-Short Form (PSDQ-SF) in Kannada language and check its validity and reliability. Materials and Methods: The English version of PSDQ-SF was translated into Kannada language using the WHO guidelines. Content validity and face validity were assessed with the help of six experts. Amendments were made to get the final synthesized version. The final version of the translated tool was given to 150 parents of children aged between 6 and 12 years to test its reliability. Results: An acceptable item-level content validity index (I-CVI values ranging from 0.83 to 1) and scale-level content validity index (S-CVI values ranging from 0.98 to 0.99) were obtained. The face validity was tested on the basis of consensus among the translators, investigators, and six experts (index of clarity – 98.4%). Acceptable internal consistency was obtained for total scale (Cronbach’s alpha = 0.72). For subscales, it was found to be good for authoritative (Cronbach’s alpha = 0.83), acceptable for authoritarian (Cronbach’s alpha = 0.75), and questionable for permissive (Cronbach’s alpha = 0.60). The test–retest reliability score was 0.80 which reflected excellent reliability. Conclusions: The Kannada version of PSDQ-SF was found to be valid and reliable with acceptable to good scores. Hence, it can be used on Kannada-knowing population by dental health professionals in their clinical practice as well as for research purposes.